Multi-scale modeling of damage development in a thermal barrier coating - Saucedo-Mora, L; Slámečka, K; Thandavamoorthy, U; Marrow, T (Elsevier, 2015)
A multi-scale Finite Element Microstructure MEshfree (FEMME) fracture model for quasi-brittle materials with complex microstructures is applied to simulate thermo-mechanical damage in a plasma-sprayed thermal barrier coating system. This novel multi-scale technique for damage simulation allows the influence of the microstructure of the yttria-stabilized zirconia top coat and the geometry of the bond coat and the thermally grown oxide layer to be considered with computational efficiency. Mechanical damage, due to the thermal strain of an applied temperature difference, is predicted to decrease the top coat Young's modulus. The interaction between the evolution of damage and temperatures within the top coat is also simulated, demonstrating the capability of this methodology to address coupled multi-scale problems.